2015
DOI: 10.1038/srep14478
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-37 contributes to the immunosuppressive property of human CD4+CD25+ regulatory T cells

Abstract: Interleukin-37 (IL-37) possesses the function of down-regulate systemic and local inflammation. It is unknown whether IL-37 is expressed in human regulatory T cells (Tregs) and its role in modulating the immune response of Tregs. In the present study, cell surface molecules and secretory cytokines were analyzed in order to determine the function of IL-37 in regulating inhibitory effect of human CD4+CD25+Tregs. Meanwhile, the effects of IL-37 on T cell differentiation and proliferation as co-culture of CD4+CD25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…As we have recently shown, silencing IL-37 in human CD4 + CD25 + Tregs obviously reduced the suppressive activity of CD4 + CD25 + Tregs30. In the current study, the aims were to determine whether recombinant human IL-37 (rhIL-37) enhanced the suppressive activity of CD4 + CD25 + Tregs in the presence or absence of LPS.…”
mentioning
confidence: 93%
“…As we have recently shown, silencing IL-37 in human CD4 + CD25 + Tregs obviously reduced the suppressive activity of CD4 + CD25 + Tregs30. In the current study, the aims were to determine whether recombinant human IL-37 (rhIL-37) enhanced the suppressive activity of CD4 + CD25 + Tregs in the presence or absence of LPS.…”
mentioning
confidence: 93%
“…Furthermore, we observed a Th1 expansion in the spleen of IL-37-Tg mice infected with BCG. The expression of IL-37 in CD4+ T cells was reported previously [16], therefore it’s potentially interesting to investigate its direct effect on the differentiation of Th1 cells and the precise underlying mechanism.…”
Section: Discussionmentioning
confidence: 92%
“…We found that IL-37 was highly presented in the lung at all time points examined in the transgenic mice but not the WT mice, and an elevated IL-37 abundance was observed as early as 1 week post infection (Fig 1F). Since the ROSA26 promoter drives gene expression constitutively and ubiquitously, the increased IL-37 in the lung of transgenic mice post infection could be due to increased frequencies and numbers of cells expressing IL-37 including macrophages, dendritic cells and regulatory T cells [11,16]. Overall, recognition of mycobacteria by macrophages led to the induction of IL-37, which may contribute to elevated IL-37 in BCG-infected mice and TB patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, IL-35, a member of IL-12 family, was identified in mice as an inhibitory cytokine produced by Tregs which are involved in their suppressive function [88]. Recently, it was shown that Tregs obtained from human peripheral blood produce IL-37 to cause T-cell immunosuppression [89]. Studies performed in mice point to an additional mechanism of immune modulation by Tregs, consisting in the secretion of microvesicles.…”
Section: Regulatory T-cellsmentioning
confidence: 99%